DIPLOMASI PUBLIK : HUBUNGAN YOUTUBE "TARAWONI TV" TERHADAP MENINGKATNYA MINAT MASYARAKAT INDONESIA PADA BUDAYA KOREA SELATAN - Tiara Putri Lestari, (2023)
This study aims to discuss the relationship between YouTube channels and diaspora, which can also be said to be non-state actors as a new style of diplomacy from individual to individual. By using an analytical knife in the form of international broadcasting theory, the concept of diaspora and the concept of public diplomacy. The method used is qualitative-descriptive for the data collected from primary and secondary sources. Researchers used four stages in analyzing the data obtained, namely collection, reduction, presentation of data in the form of tables to conclusions and data validity. The results obtained from data processing in this study explain that the YouTube channel has active involvement in the implementation of public diplomacy. Judging from the data they have, the role of the diaspora is to actively provide information and utilize digital media as a tool for diplomacy. It is known that the display of content on the YouTube channel is informative and easy to understand so that all viewers can easily understand, are interested and without realizing it they are able and successful in influencing public opinion.